Obesity is Not Associated with Increased Short‐term Complications After Primary Total Shoulder Arthroplasty. Issue 3 (March 2016) - Jiang, Jimmy J.; Somogyi, Jason R.; Patel, Pranay B.; Koh, Jason L.; Dirschl, Douglas R.; Shi, Lewis L.
Abstract: Background: Few studies have analyzed the association between elevated BMI and complications after total shoulder arthroplasty (TSA). Previous studies have not consistently arrived at the same conclusion regarding whether obesity is associated with a greater number of postoperative complications. We used a national surgical database to compare the 30‐day complication profile and hospitalization outcomes after primary TSA among patients in different BMI categories. Questions/purposes: We asked: (1) Is obesity associated with an increased risk of complications within 30 days of primary TSA? (2) Is obesity associated with increased operative time? Methods: The American College of Surgeons National Surgical Quality Improvement Program ® database for 2006 to 2012 was queried to identify all patients who underwent a primary TSA for osteoarthritis of the shoulder. The ACS‐NSQIP ® database was selected for this study as it is a nationally representative database that provides prospectively collected perioperative data and a comprehensive patient medical profile. Exclusion criteria included revision TSA, infection, tumor, or fracture. We analyzed 4796 patients who underwent a primary TSA for osteoarthritis of the shoulder. Patients who underwent a TSA were divided in four BMI categories: normal (18.5‐25 kg/m 2 ), overweight (25‐30 kg/m 2 ), obesity Class 1 (30‐35 kg/m 2 ), and obesity Class 2 or greater (> 35 kg/m 2 ). Perioperative hospitalization data and 30‐day postoperative complications were compared among different BMI classes. Differences in patient demographics, preoperative laboratory values, and preexisting patient comorbidities also were analyzed among different BMI groups, and multivariate analysis was used to adjust for any potential confounding variables. Results: There was no association between BMI and 30‐day complications after surgery (normal as reference, overweight group relative risk: 0.57 [95% CI, 0.30‐1.06], p = 0.076; obesity Class 1 relative risk: 0.52 [95% CI, 0.26‐1.03], p = 0.061; obesity Class 2 or greater relative risk: 0.54 [95% CI, 0.25‐1.17], p = 0.117). However, greater BMI was associated with longer surgical times (for normal BMI control group: 110 minutes, SD, 42 minutes; overweight group: 115 minutes, SD, 46 minutes, mean difference to control: 5 minutes [95% CI, −1 to 10 minutes], p = 0.096; obesity Class 1: 120 minutes, SD, 43 minutes, mean difference: 10 minutes [95% CI, 5‐15 minutes], p < 0.001; obesity Class 2 or greater: 122 minutes, SD, 45 minutes, mean difference: 12 minutes [95% CI, 6‐18 minutes], p < 0.001). Conclusions: Although the surgical time increased for patients with greater BMI, the 30‐day complications and perioperative hospitalization data after TSA were not different in patients with increased BMI levels. Obesity alone should not be a contraindication for TSA, and obese patients can expect similar incidences of postoperative complications. The preoperative medical optimization plan should be consistent with that of patients who are not obese who undergo TSA. Level of Evidence: Level III, therapeutic study.